2014
DOI: 10.1111/jnc.12702
|View full text |Cite
|
Sign up to set email alerts
|

3D Electrospun scaffolds promote a cytotrophic phenotype of cultured primary astrocytes

Abstract: Astrocytes are a target for regenerative neurobiology because in brain injury their phenotype arbitrates brain integrity, neuronal death and subsequent repair and reconstruction. We explored the ability of 3D scaffolds to direct astrocytes into phenotypes with the potential to support neuronal survival. Poly-e-caprolactone scaffolds were electrospun with random and aligned fibre orientations on which murine astrocytes were sub-cultured and analysed at 4 and 12 DIV. Astrocytes survived, proliferated and migrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 50 publications
3
67
0
Order By: Relevance
“…Such cultures take longer to become confluent and whilst they too express high levels of GLAST; GLT-1 levels decrease over time, with the functional burden of glutamate transport assumed by GLAST [48,50]. Indeed, research has shown that GLAST mediates the majority of L-glutamate uptake in postnatal cortical astrocyte cultures (28)(29)(30)(31)(32)(33)(34)(35), correlating with increased cell surface expression of GLAST [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such cultures take longer to become confluent and whilst they too express high levels of GLAST; GLT-1 levels decrease over time, with the functional burden of glutamate transport assumed by GLAST [48,50]. Indeed, research has shown that GLAST mediates the majority of L-glutamate uptake in postnatal cortical astrocyte cultures (28)(29)(30)(31)(32)(33)(34)(35), correlating with increased cell surface expression of GLAST [22].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the intriguing notion that reduced astrocyte reactivity is associated with lower levels of GLT-1. In disease or animal disease models, under conditions where astrocytes up-regulate GFAP there is often down-regulation of GLT-1 eg in Motor Neuron Disease [22,30,51]. Loss of GLT-1 during astrocyte reactivity is often associated with a loss of protective functions in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12), nanogels may be designed for therapeutic delivery [151,152]. Macroscopic hydrogels/scaffolds may be designed for neuron guidance applications, cell delivery systems or growth factor/drug depots for sustained release [153][154][155][156]. Network formation may be induced via a variety of methods.…”
Section: Cross-linked Networkmentioning
confidence: 99%